Subspecific taxonomy of the desert locust, Schistocerca gregaria (Orthoptera: Acrididae), based on molecular and morphological characters. (1st March 2016) - CHAPUIS, MARIE‐PIERRE; BAZELET, CORINNA S.; BLONDIN, LAURENCE; FOUCART, ANTOINE; VITALIS, RENAUD; SAMWAYS, MICHAEL J.
Abstract: We evaluated the validity of the subspecific designation for Schistocerca gregaria gregaria (Forskål) and Schistocerca gregaria flaviventris (Burmeister), isolated in distinct regions along the north–south axis of Africa. Towards this goal, we assessed the variation of multiple morphological and molecular traits within species. We first used elliptic Fourier and landmark‐based relative warps analyses to compare the size and shape of two internal and two external structures of male genitalia. We provide a discriminant function which classified the specimens with 100% accuracy and selected shape elements of the external structures only (cercus and epiproct). We also tested eight molecular markers, and because of either absence of variation or contamination by mitochondrial DNA (mtDNA)‐like sequences, we used a clone‐and‐sequence analysis of the standard cytochrome c oxidase subunit I mitochondrial DNA barcode only. We differentiated 185 true mitochondrial sequences from 66 mitochondrial DNA‐like sequences, most of which were from S. g. gregaria specimens. On the dataset of mitochondrial origin, we identified three characteristic point mutations that diagnosed the two allopatric subspecies with 94% accuracy. Minimum spanning network and parsimony tree analyses identified S. g. flaviventris as a monophyletic lineage distinct from the nominate subspecies. Accordingly, microsatellite data indicate rarely occurring admixture events only, showing that independent evolutionary history is the norm.